PEMBERDAYAAN PKK DESA LINGGASARI MELALUI PELATIHAN PRODUKSI DAN PENINGKATAN DIVERSIFIKASI KEMASAN DODOL BENGKUANG - Hernowo, Hernowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2025)
Micro, Small and Medium Enterprises (MSMEs) play an essential role in economic stability. MSMEs assistance through empowerment activities is a positive stimulus to upgrade MSMEs. Identification of regional potential is an integral part of MSME empowerment activities. Identification of regional potential functions in mapping the superior potential of an area. Linggasari Village is one of the villages in Kembaran Sub-district with the highest bengkuang potential in Banyumas Regency. However, the potential of bengkuang has not been optimally processed. Through training activities on production and packaging diversification in the Family Empowerment and Welfare (PKK) group, it is expected to be able to mobilize the community, especially PKK mothers, to be able to contribute to the family economy through the UMKM forum. This empowerment activity is a form of Community Service (PkM) which is carried out using a combination of two methods, namely Focus Group Discussion (FGD) and Participatory Learning and Action (PLA). The results of the PkM activities showed that the PKK of Linggasari Village was very enthusiastic in the implementation of production training and diversification of bengkuang dodol product packaging. The evaluation of PkM activities shows that with the training and mentoring that is in accordance with the needs of the Linggasari Village PKK, it has a positive impact on improving the skills of a person. Good cooperation between the Linggasari Village government, the Linggasari Village PKK, enablers, and internal Linggasari Village business actors not only facilitates implementation but also in developing Linggasari Village MSMEs.